Kualitas Kehidupan Kerja dalam memprediksi Kompetensi dengan perantara Komitmen Organisasional - Askafi, Eka (Universitas Islam Kadiri, 2025)
ABSTRACT The objective of this study is to examine the effect of kualitas kehidupan kerja on organizational commitment, also testing the effect of quality of worklife on competence and the effect of kualitas kehidupan kerja on competence with the effect of kualitas kehidupan kerja on organizational commitment organizational commitment as mediating. The population and sample in this study were all vocational high school teachers about 208 teachers in Kendal Indonesia using Proportionate Random Sampling. The data analysis in this study is Stuctural Equation Modelling (SEM) using software AMOS 26.0 with the result kualitas kehidupan kerja spirituality have a significant effect on organizational citizenship behavior. These results indicate that good kualitas kehidupan kerja teachers as theirs commitment and kualitas kehidupan kerja can encourege teachers to good performance. It is necessary to improve teacher performance by periodically assessing teaching performance through evaluation indicators in accordance with Indonesian Law No. 14 of 2005, so that teachers, in carrying out the learning programs, do not go in the wrong direction, always base their work on the basic competence syllabus, and provide learning facilities/media so that teachers can use learning media as support for classroom teaching and learning activities to enhance students' motivation and academic achievement. Key words: kualitas kehidupan kerja, Commitment, Competence